2015
DOI: 10.17219/acem/40464
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of the Influence of the Method for Obtaining Hemostasis on the Occurrence of Postoperative Complications after Thyroid Surgery

Abstract: Background. The need to obtain successful surgical hemostasis had a significant impact on the development of electrosurgery. Innovative technical solutions necessitate the continuous training of surgeons in the use of more modern technologies. The diversity of solutions is also associated with the need to adapt the methods for obtaining hemostasis to the type of operation. Each time, the introduction of new technologies requires a critical evaluation of the results of surgical treatment. The most important mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The use of instruments as the harmonic scalpel and radiofrequency or thermal devices also improves vessel sealing and several studies confirm their effectiveness to prevent hemorrhagic events [ 7 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of instruments as the harmonic scalpel and radiofrequency or thermal devices also improves vessel sealing and several studies confirm their effectiveness to prevent hemorrhagic events [ 7 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Praženica et al [38] reported permanent hypocalcemia in 1.5% of their cases. The traditional method for obtaining hemostasis is tying off and ligation of the cut vessels, ultrasonic vibration and bipolar electrocoagulation [39] . Grajek et al [39] reported in their study that the incidence of permanent RLN palsy and hypocalcemia were 0.8% and 2.4% in those who underwent bipolar electrocoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional method for obtaining hemostasis is tying off and ligation of the cut vessels, ultrasonic vibration and bipolar electrocoagulation [39] . Grajek et al [39] reported in their study that the incidence of permanent RLN palsy and hypocalcemia were 0.8% and 2.4% in those who underwent bipolar electrocoagulation. However, the 4 techniques described in the current study reported the lowest incidence of permanent RLN palsy (0.16%) and hypocalcemia (0.3%).…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the bipolar electrosurgical cautery is associated with less thermal effect leading to a significant reduction in the incidence of recurrent laryngeal nerve injury and postoperative hypoparathyroidism. [29]…”
Section: Discussionmentioning
confidence: 99%